Perceived Influence of Social Media Content Creation on Unemployment in Lagos Island - Olalekan Olubamike Olufemi; Sunday Ogbonna; Timothy Ekeledirichukwu Onyejelem; Olayinka Babatunde Adebogun (Budapest International Research and Critics University, 2025)
This study x-rays the perceived influence of social media content creation on unemployment in Lagos Island. The study was anchored on the Uses and Gratifications Theory and the Teno Proactive Communication Model for Job Creation in Nigeria. Survey research method was used and 400 respondents were purposively selected in Lagos Island. Data were presented in frequency and percentage counts, however, the hypotheses were tested using One Sample T-Test where the p-value was less than 0.05 level of significance. Findings from the study revealed that 87% of the residents of Lagos Island have access to smartphone which gave them opportunity to use various social media applications like Facebook, WhatsApp, XApp, Instagram and TikTok. Also, it was discovered that social media content creation has helped some youths to be self-independent, through content creation 92%. A well edified contents on social media serve as means of income when monetized 96% and it also helps in promoting one’s talents, giving room to partake in movie production. More so, the use of various social media applications like Facebook, Instagram, TikTok among others help youths to make income through marketing of other peoples’ products or brands 95%. The study however concluded that social media content creation is an employment mechanism among the youths in Lagos Island, making more than average number of the youths to seize the opportunity in self-employment. The study recommended that Content creators should ensure they post relevant and accurate information online to avoid misleading social media users